Strategy in Conserving and Marketing Songket Woven Fabrics at Kota Daro I Village - I Dewa Gede Ari Pemayun; H. Wawan Ahmad Ridwan; Khairiyatun Sholihah; Nasrullah Nasrullah; Putri Hana Pebriana (Utan Kayu Publishing, 2023)
This research was conducted to provide information on how to preserve and market songket woven fabrics so they can be widely spread in various cities and abroad. Based on the results of the research conducted, the results show that there are three strategies in preserving songket woven fabric in Kota Daro 1 Village, namely 1) successive strategies, namely efforts to preserve and respect traditional wisdom and local cultural values; 2) educational strategies, namely strategies that produce social actors who are appropriate and able to receive the inheritance of social groups, and can improve hierarchical levels; and 3) economic investment strategy, namely efforts to maintain capital or increase various types of capital, namely the accumulation of economic capital and social capital. Meanwhile, in marketing, songket has woven fabric in Kota Daro 1 Village; the artisans carried out a marketing strategy through promotions on social media and word of mouth. However, due to the limited Internet network and the ability of artisans to use social media to market songket woven fabrics, the marketing was not optimal